STRATEGY OF BAZNAS FOR BUILDING MUSTAḤIQ’S ECONOMIC RESILIENCE: The SWOT Analysis Perspective - Sundari Sundari; Muhammad Lathoif Ghozali (ULUL ALBAB Jurnal Studi Islam, 2022)
BAZNAS is an Indonesian agency in charge of collecting zakat and has many branches. One of the branches is in Ngawi Regency which has a program called Ngawi Makmur. It intends to realize family welfare and resilience by helping Micro, Small, and Medium Enterprises and people in debt. This is a qualitative study aiming to reveal the strategy of BAZNAS Ngawi in building family economic resilience. This is a type of field research which involve mustah{iq receiving financial assistance in 6 sub-districts. The data are collected using observation, interviews, and documentation. They were then validated by triangulation, comparing the results of interviews and observation. The obtained data were then analyzed in three stages, namely data simplification, data presentation, and drawing conclusion. BAZNAS Ngawi's strategy is to prioritize the SO (Strengths-Opportunities) by improving the skills of mustah{iq, providing training and assistance to housewives, and collaborating with OPZ to form social enterprises for mustah{iq. Based on the results of the SWOT analysis, BAZNAS Ngawi is in the Growth quadrant. In this quadrant, the state of the industry is in a favorable condition because it has power and can take the opportunities.